MULTILATERAL NEGOTIATIONS IN CHINA'S CURRENT RELATIONS WITH AFRICAN STATES (Вісник: Міжнародні відносини, 2024)
The proposed article is devoted to the problem of using diplomatic tools in the foreign policy of the modern state. A specific aspect of consideration is the study of multilateral negotiations in the modern relations of the PRC with African states. The research is based on a structural-functional approach to studying the work of the Forum on China-Africa Cooperation as a universal platform for multilateral cooperation and negotiations between China and African states. The author focuses attention on such issues as: 1) levels of participants in the negotiation process; 2) quality of training and competence of the participants in the negotiations; 3) negotiation style; 4) internal and external factors that determine the nature of the negotiation process.
Keywords: China, Africa, multilateralism, diplomacy, international negotiations, Forum on China-Africa Cooperation.